Miksike: USE of Estonian online tools in Ukrainian schools - Noskova, Margaryta; Mukan, Nataliya; Khamuliak, Nataliia (Lviv Politechnic Publishing House, 2017)
The analysis presented in this article is drawn from a broader qualitative study examining the experience of using online tools of the educational platformMIKSIKE (Estonia) in the EU, focusing especially on the Baltic countries, as well as its implementation in the Ukrainian schools. The authors highlight the literature review (Bykov &Ovcharuk, 2013; Hurevych & Kademiia, 2014; Morze & Vorotnikova, 2016; Mukan, Noskova & Baybakova, 2017; Patarkin, 2017a, 2017b; Robert, 2008, 2010; Vorotnikova & Kovalchuk, 2017; Zhaldak, 2005 etc.) as well as methods (theoretical methods: comparative analysis, logical and systemic analyses; applied methods: examining, inquiry, and conversations) used in this study. The researchers focus on the advantages of MIKSIKЕ online tools and their usage in the educational process. The dynamics of development and national expansion of the Project are presented. The authors analyse possibility to compare the results of different users, describe the selection of arranged mathematical exercises and problems, define the opportunity to create, store and use didactic materials on various school subjects. They determine the tool for creating test tasks of different complexity with the integrated conversion system of the obtained points into school grade.
Keywords: Pranglimine instructional training program; interactive exercises; teaching community involved in the project; educational reform; educational institution; educational online tools